Pengaruh Daya Guna, Kemudahan Aplikasi, dan Kepercayaan Pengguna terhadap Penerapan M-Pise di LPD Desa Adat Ketewel - PRIYADI, I KADEK JEPRI; BUDIASA, I WAYAN; DJELANTIK, A. A. A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The Effect of Usability, Ease of Use, and Trust on The Utilization of M-Pise at Ketewel Village Credit Institution In the current era of globalization, business competition between companies is getting tougher. Mobile banking is a development of mobile technology that is used in the commercial domain. Mobile banking combines information technology and business applications together. Everyone who has a cell phone with a mobile banking application can easily make transactions anywhere and anytime. This study aims to identify user usability, application ease of use, and trust in the utilization of digital financial technology known as M-Pise by Ketewel Village Credit Institution (LPD). The samples in this study were determined by using random sampling technique. Using multiple linear regression analysis, the study shows that user usability, application ease of use, and trust have a positive and significant effect on M-Pise utilization. The Ketewel LPD may consider providing more information related to the M-Pise application to attract customers to use it.